2020
DOI: 10.1107/s160057672000093x
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive evaluation of 3D microstructure evolution in strontium titanate

Abstract: Nondestructive X‐ray diffraction contrast tomography imaging was used to characterize the microstructure evolution in a polycrystalline bulk strontium titanate specimen. Simultaneous acquisition of diffraction and absorption information allows for the reconstruction of shape and orientation of more than 800 grains in the specimen as well as porosity. Three‐dimensional microstructure reconstructions of two coarsening states of the same specimen are presented alongside a detailed exploration of the crystallograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…[105][106][107] Nevertheless, a number of algorithms have been developed to solve the data fusion problem. For example, TriBeam data and synchrotron x-ray DCT data have been fused to study grain growth evolution in strontium titanate, 68,108 mechanical serial sectioning and nearfield x-ray HEDM information in a superalloy, 23 strain measurements by SEM-based digital image correlation (DIC) have been fused with TriBeam data to understand slip in superalloys, 86 and pore locations have been fused with TriBeam grain orientation information in tantalum 85 and an AM superalloy 70 to understand the processing routes and damage accumulation.…”
Section: Data Challenges and Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[105][106][107] Nevertheless, a number of algorithms have been developed to solve the data fusion problem. For example, TriBeam data and synchrotron x-ray DCT data have been fused to study grain growth evolution in strontium titanate, 68,108 mechanical serial sectioning and nearfield x-ray HEDM information in a superalloy, 23 strain measurements by SEM-based digital image correlation (DIC) have been fused with TriBeam data to understand slip in superalloys, 86 and pore locations have been fused with TriBeam grain orientation information in tantalum 85 and an AM superalloy 70 to understand the processing routes and damage accumulation.…”
Section: Data Challenges and Opportunitiesmentioning
confidence: 99%
“…In 2020, a commercial TriBeam instrument 63 was announced by Thermo Fisher Scientific (which acquired FEI in 2016). The existing prototype version of the TriBeam microscope has produced 3D data at unprecedented sizes and sectioning speeds, 60,64 thus facilitating understanding of the role of 3D twin structures in initiating fatigue cracks in nickel superalloys [65][66][67] and studies of grain growth in strontium titanate, 68 produced datasets for simulation of the mechanical properties for a range of titanium alloy processing conditions, 69 quantified defects and microstructure prediction in metal additive manufacturing, 70,71 and quantified permeability and fluid flow properties of tungsten copper composites in 3D. 45 A prototype load-lock coupled femtosecond laser machining system has also been built on the Zeiss Crossbeam FIB platform, 54 being commercially released in 2020.…”
Section: Introduction Background and Historymentioning
confidence: 99%
“…For instance both laboratory [49][50][51][52][53] and synchrotron x-ray imaging modes 54,55 have enjoyed continued diversification and enhancements leading to improved mapping of grain structure and crystallographic orientation compared to 3D EBSD methods. [56][57][58]…”
Section: Applicability To Other Types Of Datamentioning
confidence: 99%
“…Recently, a comparative study using DCT and nearfield HEDM to investigate the same sample, a slightly deformed (1%) aluminum alloy with an average grain size of ∼ 100 μm, showed that DCT can detect subgrain boundaries with disorientations as low as 1 • and that HEDM and DCT grain boundaries are on average 4 μm apart from each other [110]. The unique set of key advantages of DCT-the ability to repeatedly cover large volumes (1000+ grains) in a reasonable time frame (hours) with a spatial accuracy of a few micrometers enabling extraction of experimental grain boundary characters-were exploited by Trenkle and coworkers to study 3D microstructural evolution in strontium titanate [111] and Zhang and coworkers in a study of grain growth in pure iron [112]. Zhang and coworkers measured DCT grain maps at 15 timesteps during interrupted annealing at 800 • C, with timestep 1 corresponding to the initial unannealed state and timestep 15 corresponding to 75 min.…”
Section: X-ray Diffraction-contrast Tomographymentioning
confidence: 99%